1982
DOI: 10.1002/jcp.1041130509
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of cultured pre-adipose cells: A probability model

Abstract: Some cells of the established preadipose cell line, 3T3-L1, synthesize triglyceride after becoming confluent and quiescent. An analysis of the distribution of clusters of lipid-containing cells was consistent with a commitment event during exponential growth followed by clonal growth of committed cells. Experiments were designed to determine if the final clonal pattern of fat among nonfat cells could be described by a probability model. Undifferentiated cells (fibroblastic cells with no detectable accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Committed cells divide to produce clones of committed cells''. 29 Moreover, they demonstrated that ''(1) there are only two possible outcomes-either the cell commits with probability p or it does not, (2) commitment in any cell is independent of commitment in any other cell, and (3) the probability of commitment is constant during any cell cycle''. 29 In our present modeling, we were consistent with the paper of Steinberg and Brownstein 29 : given their findings with respect to mitosis, if the mother cell is committed to the adipocyte lineage, both daughter cells will be committed as well.…”
Section: The Probability Of Being Committed At Seedingmentioning
confidence: 99%
See 4 more Smart Citations
“…Committed cells divide to produce clones of committed cells''. 29 Moreover, they demonstrated that ''(1) there are only two possible outcomes-either the cell commits with probability p or it does not, (2) commitment in any cell is independent of commitment in any other cell, and (3) the probability of commitment is constant during any cell cycle''. 29 In our present modeling, we were consistent with the paper of Steinberg and Brownstein 29 : given their findings with respect to mitosis, if the mother cell is committed to the adipocyte lineage, both daughter cells will be committed as well.…”
Section: The Probability Of Being Committed At Seedingmentioning
confidence: 99%
“…29 Moreover, they demonstrated that ''(1) there are only two possible outcomes-either the cell commits with probability p or it does not, (2) commitment in any cell is independent of commitment in any other cell, and (3) the probability of commitment is constant during any cell cycle''. 29 In our present modeling, we were consistent with the paper of Steinberg and Brownstein 29 : given their findings with respect to mitosis, if the mother cell is committed to the adipocyte lineage, both daughter cells will be committed as well. If the mother cell is uncommitted, the daughter cells may both be uncommitted, or both be committed, or just one of them may be committed, depending on the stochastic parameter that determines commitment for each such individual daughter cell.…”
Section: The Probability Of Being Committed At Seedingmentioning
confidence: 99%
See 3 more Smart Citations